Lutzomyia longipalpis TGF-β Has a Role in Leishmania infantum chagasi Survival in the Vector - Di-Blasi, Tatiana; Telleria, Erich Loza; Marques, Christiane; Couto, Rodrigo de Macedo; Silva-Neves, Monique da; Jancarova, Magdalena; Volf, Petr; Tempone, Antonio Jorge; Traub-Csekö, Yara Maria (Frontiers in Cellular and Infection Microbiology, 2019)
Despite the increasing number of studies concerning insect immunity, Lutzomyia longipalpis immune responses in the presence of Leishmania infantum chagasi infection has not been widely investigated. The few available studies analyzed the role of the Toll and IMD pathways involved in response against Leishmania and microbial infections. Nevertheless, effector molecules responsible for controlling sand fly infections have not been identified. In the present study we investigated the role a signal transduction pathway, the Transforming Growth Factor-beta (TGF-) pathway, on the interrelation between L. longipalpis and L. i. chagasi. We identified an L. longipalpis homolog belonging to the multifunctional cytokine TGF- gene family (LlTGF-), which is closely related to the activin/inhibin subfamily and potentially involved in responses to infections. We investigated this gene expression through the insect development and in adult flies infected with L. i. chagasi. Our results showed that LlTGF- was expressed in all L. longipalpis developmental stages and was upregulated at the third day post L. i. chagasi infection, when protein levels were also higher as compared to uninfected insects. At this point blood digestion is finished and parasites are in close contact with the insect gut. In addition, we investigated the role of LlTGF- on L. longipalpis infection by L. i. chagasi using either gene silencing by RNAi or pathway inactivation by addition of the TGF-receptor inhibitor SB431542. The blockage of the TGF- pathway increased significantly antimicrobial peptides expression and nitric oxide levels in the insect gut, as expected. Both methods led to a decreased L. i. chagasi infection. Our results show that inactivation of the L. longipalpis TGF- signal transduction pathway reduce L. i. chagasi survival, therefore suggesting that under natural conditions the parasite benefits from the insect LlTGF-β pathway, as already seen in Plamodium infection of mosquitoes.